Pediatric Pancreatitis: Demography, Etiology, Complications and Ultrasound Findings in a Tertiary Care Centre - Sonawane, Bhawana D.; Titare, Prashant U.; Rathod, Pradip B.; Tembhekar, Narendra G.; Anand, Aarti (Current Practice in Medical Science Vol. 9, 2022)
Pancreatitis is less common in children and adolescents than in adults, and the causes in adults and children are different. The objective was to study demography, etiology, complications and detail ultrasound findings in pediatric pancreatitis. Retrospectively, 20 patients were evaluated for demographics, etiology, complications, and transabdominal ultrasound findings showing a common presentation in the 10- to 15-year-old age group with predominantly female patients. Acute and chronic pancreatitis were noted in two and eighteen cases, respectively. Idiopathic cause and chronic variant most commonly observed in our study population. Pseudocyst and ascites were the most common complications of pancreatitis found in our study. Ultrasound is an important first-line test that can be used in the diagnosis, classification, and follow-up of pediatric pancreatitis.